2018
DOI: 10.1021/acsphotonics.7b01384
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial VO2 Nanostructures: A Route to Large-Scale, Switchable Dielectric Metasurfaces

Abstract: Metasurfaces offer unparalleled functionalities for controlling the propagation and properties of electromagnetic waves. But to transfer these functions to technological applications, it is critical to render them tunable and to enable fast control by external stimuli. In most cases, this has been realized by utilizing tunable materials combined with a top-down nanostructuring process, which is often complicated and time intensive. Here we present a novel strategy for fabricating a tunable metasurface comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…This reversible phase transition is the result of an interplay between Mott‐ and Peierls‐type mechanisms, and can result in carrier‐density changes of up to four orders of magnitude across the IMT . The dramatic change in optical properties of VO 2 that accompanies the carrier‐density change has advanced a variety of applications, including optical limiting, nonlinear isolation, switching, and thermal‐emission engineering . Depending on the VO 2 film quality, grain size, the concentration and type of potential impurities, and the degree of strain, the phase transition can vary from abrupt to gradual .…”
Section: Introductionmentioning
confidence: 99%
“…This reversible phase transition is the result of an interplay between Mott‐ and Peierls‐type mechanisms, and can result in carrier‐density changes of up to four orders of magnitude across the IMT . The dramatic change in optical properties of VO 2 that accompanies the carrier‐density change has advanced a variety of applications, including optical limiting, nonlinear isolation, switching, and thermal‐emission engineering . Depending on the VO 2 film quality, grain size, the concentration and type of potential impurities, and the degree of strain, the phase transition can vary from abrupt to gradual .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, if installed on spacecraft and satellites, the proposed optical solar reflector is expected to maintain system temperature in an optimal range through self‐regulated thermal emission according to the device temperature in space. Ito et al reported the emission control of a VO 2 resonator–insulator–tungsten metasurface, while Ligmajer et al recently demonstrated temperature tunable optical responses from an epitaxially grown VO 2 nanobeam based metasurface . It should be noted that, in addition to the top‐down methods, solution‐processable colloidal synthesis of VO 2 nanocrystals and assembly techniques that have been reported recently provide an alternative approach to achieving active photonic metasurfaces that exhibit reversible IMT …”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Thanks to its switchable polarization dependence (from weak to strong), the nanomaterial can thus be used as a switchable near‐infrared polarizer. The authors also demonstrated how to use it as a switchable near‐infrared phase shifter in the optical telecom window …”
Section: Plasmon Resonancesmentioning
confidence: 99%
“…b) Extinction spectra by far‐field transmittance measurements at normal incidence with the incident light polarized along the long axis of the nanoparticle and perpendicular to it at room temperature (below the dielectric–metal transition, plasmons off) and at 80° (above the transition, plasmons on). Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Plasmon Resonancesmentioning
confidence: 99%
See 1 more Smart Citation